Compete by bursting the bubble how MinuteClinic met the unmet health care needs of millions--cheaply and conveniently - Champy, James 1942- (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from Inspire!: why customers come back (ISBN: 9780131361881) by Jim Champy. MinuteClinic's founders were bubble bursters, creative guerrillas who thrive on outsmarting complacent companies in industries that run on tired ideas. Bubble bursters come in all cultural shapes and financial sizes, but share one indispensable trait: They see what others can't, and act on it by applying solid practices everyone else agrees are irrelevant"--Resource description page.
Keywords: Ambulatory medical care -- United States; Clinics; Success in business; Branding (Marketing); Traitement ambulatoire; États-Unis; Succès dans les affaires; Stratégie de marque; branding; Ambulatory medical care; United States